Analisis Implementasi Fungsi Manajemen Pada Unit Informasi Dalam Meningkatkan Pelayanan Di Bandar Udara Internasional I Gusti Ngurah Rai Bali - Wulan Nurhikmah; Anita Nur Masyi’ah (Jurnal Kajian dan Penelitian Umum, 2023)
Management is an important aspect needed by a working unit or even in carrying out activities. Therefore, one of the research studies conducted is the analysis of the implementation of management functions in the information unit to improve services at Ngurah Rai International Airport Bali. The purpose of this study is to analyze the implementation of management functions carried out by the information unit to improve the services provided. This research also aims to identify the obstacles and solutions implemented by the information unit when providing services. This research uses qualitative research methods, conducted in June 2023, located at Ngurah Rai International Airport Bali. Data collection techniques were done through interviews, observations, and documentation. Data validity was tested using the triangulation of techniques and sources. The data analysis techniques used were data collection, data reduction, data presentation, and drawing conclusions. The research results show that the Information Unit has implemented management functions such as planning, organizing, directing, and controlling to enhance the provided services. However, based on service indicator measurements, there were deficiencies found in the responsiveness and empathy indicators, which are the result of poor organizing function performed by the Information Unit. Service constraints were also identified, such as FIDS error, SIOPSKOM Inalix system downtime, miscommunication between information officers and airline staff, and insufficient number of information unit personnel, which hindered optimal service delivery. The Information Unit's solution is to contact the relevant working units regarding the damages, make manual announcements if necessary, double check the requests from airline staff, and have supervisors assist if the information unit personnel become overwhelmed.